Stepwise Reduction of Graphene Oxide (GO) and Its Effects on Chemical and Colloidal Properties - Samar Azizighannad (Nature Portfolio, 2018)
Abstract Graphene Oxides (GO) typically contains different oxygen containing groups such as hydroxyl, carboxyl and epoxy, and reduced GO (r-GO) represents a family of material with diverse chemical properties. In an effort to understand how properties of r-GO change as GO is reduced, a stepwise reduction of the same GO to r-GO containing different levels of oxygen was carried out, and their corresponding chemical and colloidal properties are reported. Starting with GO containing 49 percent oxygen, r-GOs containing 31, 19 and 9 percent oxygen were synthesized. The aqueous behavior in terms of solubility gradually decreased from 7.4 µg/ml for GO to nearly zero for r-GO with 9% oxygen, while dispersibility under sonication decreased from 8 to 2.5 µg/ml for the same samples. Hydrophobicity index as measured as the octanol water partition coefficient decreased from −3.89 to 5.2% as oxygen content dropped from 49 to 9%. Colloidal behavior was also dramatically affected by reduction, and critical coagulation concentration (CCC) dropped from 28 to 15 in presence of 0.5 mmole/l NaCl and from 6 to 2 in presence of 0.5 mmole/l MgCl2 as the oxygen in the original GO was reduced to 9%.